Structure-activity relationships and mechanism of action of tetragomycin derivatives as inhibitors of Staphylococcus aureus staphyloxanthin biosynthesis. (July 2020) - Ribeiro, L.M.B.C.; Fumagalli, F.; Mello, R.B.; Froes, T.Q.; da Silva, M.V.S.; Villamizar Gómez, S.M.; Barros, T.F.; Emery, F.S.; Castilho, M.S.
Abstract: Despite the main strategy to overcome bacterial resistance has focused on the development of more potent antimicrobial agents, the evolutionary pressure caused by such drugs makes this strategy limited. Molecules that interfere with virulence factors appear as a promising alternative though, as they cause reduced selective pressure. As a matter of fact, staphyloxanthin biosynthesis inhibition (STXBI) has been pursued as promising strategy to reduce S. aureus virulence. Herein, we report the inhibitory profile of 27 tetrangomycin derivatives over staphyloxanthin production. The experimental result showed that naphthoquinone dehydro- α -lapachone (25 - EC50  = 57.29 ± 1.15  μ M) and 2-Isopropylnaphtho[2, 3- b ]furan-4, 9-dione (26 EC50  = 82.10 ± 1.09  μ M) are the most potent compounds and suggest that hydrogen acceptor groups and lipophilic moieties decorating the naphthoquinone ring are crucial for STXBI. In addition, we present an in situ analysis, through RAMAN spectroscopy, that is inexpensive and might be employed to probe the mechanism of action of staphyloxanthin biosynthesis inhibitors. Therefore, our molecular simplification strategies afforded promising lead compounds for the development of drugs that modulate S. aureus staphyloxanthin biosynthesis. Highlights: Tetrangomcycin derivates inhibit staphyloxanthin production in  S. aureus. RAMAN spectroscopy allows i n situ  analysis of  S. aureus  carotenoid profile. Naphthoquinone dehydro- α -lapachone (25 ) inhibits staphyloxanthin production (EC50 = 57.29 ± 1.15  µ M ). Compound 25 effect over  S. aureus'  carotenoid profile is more similar to terbinafine's than to farnesol's.